2006
DOI: 10.1094/pd-90-1457b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Cucumber mosaic virus Subgroup II Infecting Lycopersicon esculentum in India

Abstract: During a survey in January 2006 near Salem in Tamil Nadu (south India), Cucumber mosaic virus was observed infecting tomatoes with an incidence of more than 70%. Plants exhibiting severe mosaic, leaf puckering, and stunted growth were collected, and the virus was identified using diagnostic hosts, evaluation of physical properties of the virus, compound enzyme-linked immunosorbent assay (ELISA) (ELISA Lab, Washington State University, Prosser), reverse-transcription polymerase chain reaction (RT-PCR), and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Mainly, subgroup I isolates has been reported and there are few reports of subgroup II isolates [1,15,47,53]. The isolate under study showed up to 99 and 76 % similarity to the subgroup II and I isolates, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Mainly, subgroup I isolates has been reported and there are few reports of subgroup II isolates [1,15,47,53]. The isolate under study showed up to 99 and 76 % similarity to the subgroup II and I isolates, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Previously, shoestring like leaves symptoms were reported only with some subgroup I strains [2,20,32,46,48]. From India also there was report of mosaic symptoms on tomato by subgroup II strain [47] and now in a recent observation it was found that shoestring symptoms were not restricted to subgroup I. A subgroup II isolate Tss-In developed shoestring symptoms on tomato [15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In India, CMV infecting tomato was characterized on the basis of biological and serological level by Kiranmai et al [6,7]. Restriction fragment length polymorphism analysis of the PCR product of the CP region of a subgroup II CMV strain causing severe mosaic on tomato in south India was also reported [25]. The association of CMV with shoestring symptoms of tomato for the first time in India was identified by us [16].…”
mentioning
confidence: 99%
“…In India, the occurrence of CMV has been reported from many hosts such as Egyptian henbane (Samad et al, 2000), gladiolus (Raj et al, 2002), Lycopersicum esculentum (Sudhakar et al, 2006), Geranium (Verma et al, 2006), banana (Aglave et al, 2007), Rauvolfia serpentina and Jatropha curcas (Raj et al, 2007(Raj et al, , 2008. However, only limited reports are available on biological and molecular characteristics of these isolates (Madhubala et al, 2005, Verma et al, 2004.…”
Section: Introductionmentioning
confidence: 99%